PENGEMBANGAN MEDIA PEMBELAJARAN MIND MAPPING BERBANTUAN APLIKASI CANVA PADA IPAS MATERI DAERAHKU KEBANGGAANKU KELAS V SD - Amira, Amira Qhistina; Beta Rapita Silalahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the challenges in the IPAS (Science and Social Studies Integration) learning processin Grade V of elementary school is the low student interest in the topic “My Proud Region,”which is taught by highlighting the Batak Karo ethnic group of Biru-Biru. The lack of varietyin learning media is a major factor contributing to the low student participation inunderstanding the material. This study aims to design and develop Mind Mapping learningmedia using the Canva application to enhance students' understanding and engagementduring the learning process. The approach used is Research and Development (R&D) withthe ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Thesubjects of this research are Grade V students of SD Negeri 101812 Namo Tualang BiruBiru. Data collection techniques include observation and expert validation questionnaires(content, media, and language), as well as trials with teachers and students. The resultsshow that the Mind Mapping learning media using Canva is considered highly feasible.Validation results from content experts reached an average of 82.4%, media experts 78%,and language experts 94.6%, all of which fall into the